Analysis of NH3‐TPD Profiles for CuSSZ‐13 SCR Catalyst of Controlled Al Distribution – Complexity Resolved by First Principles Thermodynamics of NH3 Desorption, IR and EPR Insight into Cu Speciation. Issue 68 (23rd November 2021) - Mozgawa, Bartosz; Zasada, Filip; Fedyna, Monika; Góra‐Marek, Kinga; Tabor, Edyta; Mlekodaj, Kinga; Dědeček, Jiří; Zhao, Zhen; Pietrzyk, Piotr; Sojka, Zbigniew
Abstract: NH3 temperature‐programmed desorption (NH3 ‐TPD) is frequently used for probing the nature of the active sites in CuSSZ‐13 zeolite for selective catalytic reduction (SCR) of NOx . Herein, we propose an interpretation of NH3 ‐TPD results, which takes into account the temperature‐induced dynamics of NH3 interaction with the active centers. It is based on a comprehensive DFT/GGA+D and first‐principles thermodynamic (FPT) modeling of NH3 adsorption on single Cu 2+, Cu +, [CuOH] + centers, dimeric [Cu‐O‐Cu] 2+, [Cu‐O2 2− ‐Cu] 2 species, segregated CuO nanocrystals and Brønsted acid sites (BAS). Theoretical TPD profiles are compared with the experimental data measured for samples of various Si/Al ratios and distribution of Al within the zeolite framework. Copper reduction, its relocation, followed by the intrazeolite olation/oxolation processes, which are concomitant with NH3 desorption, were revealed by electron paramagnetic resonance (EPR) and IR. DFT/FPT results show that the peaks in the desorption profiles cannot be assigned univocally to the particular Cu and BAS centers, since the observed low‐, medium‐ and high‐temperature desorption bands have contributions coming from several species, which dynamically change their speciation and redox states during NH3 ‐TPD experiment. Thus, a rigorous interpretation of the NH3 ‐TPD profiles of CuSSZ‐13 in terms of the strength and concentration of the active centers of a particular type is problematic. Nonetheless, useful connections for molecular interpretation of TPD profiles can be established between the individual component peaks and the corresponding ensembles of the adsorption centers. Abstract : Interpretation of NH3 ‐TPD results, which takes into account the temperature‐induced dynamics of NH3 interaction with the active centers of CuSSZ‐13 is proposed. It is based on DFT/GGA+D and first principles thermodynamic modeling of various monomeric and polymeric Cu species, segregated CuO and Brønsted acid sites. Comprehensive interpretation includes Cu reduction, its relocation and oxolation, which are concomitant with ammonia desorption.